Disruption of CD40 Results in Significantly Attenuated Renal Inflammation Following Glycerol-Induced Acute Kidney Injury - Zhang, Shungang (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.